2021
DOI: 10.1063/5.0061856
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited of ultrathin VOx-doped NiFe layer on porous NiCo phosphide for efficient overall water splitting

Abstract: An ultrathin VOx-doped NiFe alloy layer (VOx@NiFe) was electrodeposited on the surface of nickel-cobalt phosphide (NiCoP) supported by titanium mesh (TM) to achieve a highly active and low-cost bifunctional electrocatalyst for overall water splitting. VOx doping not only significantly enhances the electrochemical surface areas and the concentration of oxygen vacancies in the NiFe/NiCoP/TM composite, but also greatly improves the surface hydrophilicity. The VOx@NiFe/NiCoP/TM electrode retains a 3D porous struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…This finding suggested that N-doping could endow the electrode surface with superior wettability, thereby facilitating the dissipation of gas bubbles and improving the catalytic performance significantly. 36 In situ conversion reconstructed the morphology into a 3D nanosheet network and provided an enlarged specific surface area for abundant active sites. The optimal monolithic electrode yielded massive oxygen bubbles under high current density.…”
mentioning
confidence: 99%
“…This finding suggested that N-doping could endow the electrode surface with superior wettability, thereby facilitating the dissipation of gas bubbles and improving the catalytic performance significantly. 36 In situ conversion reconstructed the morphology into a 3D nanosheet network and provided an enlarged specific surface area for abundant active sites. The optimal monolithic electrode yielded massive oxygen bubbles under high current density.…”
mentioning
confidence: 99%